الطاغوت في ضوء القرآن - Shawkat Taha Ali Talafihah; Mohd. Fauzi Mohd. Amin; Muhammad Mustaqim Mohd.Zarif (Universiti Sains Islam Malaysia, 2024)
The word thaghut is mentioned in various places of the Quran, both in Meccan and Medinan verses. It is a term that is commonly used by scholars and preachers in various meanings and connotations ranging from a moderate understanding to the extreme interpretation. In this paper, an attempt is made to expound a detailed understanding of the meaning of the term thaghut in the Quran, its types and implementation in the field of Islamic propagation as well as its implications. In general, the paper is divided into two sections. The first part analyses the concept of thaghut while the second part discusses its methods and purposes. In its findings, the study presents a comprehensive concept of thaghut in the Quran that includes false deities and those who are against the rules of Allah whether in the form of demon, idol, human or others. Similarly, it also highlights the various methods and means of spreading false ideology of thaghut through knowledge, mass media, trickery and others. The various types of thaghut worship are also explained together with its implications both in this world and in the hereafter.